The Role of Estrogen Receptor α in Response to Longitudinal Bone Growth in ob/ob Mice - Jin, Lin-Yu; Guo, Chen; Xu, Shuai; Liu, Hai-Ying; Li, Xin-Feng (Frontiers in Endocrinology, 2021)
Absence of leptin results in contrasting growth pattern of appendicular and axial bone growth in ob/ob mice. Endochondral bone formation is an important procedure of growth plate determining the bone growth, where this procedure is also regulated by estrogen and its receptor (ER) signaling pathway. The present study is undertaken to explore the roles of ERs in regulating the different growth pattern in ob/ob mice. In this study, C57BL/6 female mice were used as wild type (WT) mice, ob/ob mice and WT mice were age matched fed and bone length is analyzed by X-ray plain film at the 12-week old. we confirm that ob/ob mice have shorter femoral length and longer spine length than those of wild type mice (P<0.05). The contrasting expression patterns of chondrocyte proliferation proteins and hypertrophic marker proteins are also observed from the femur and spinal growth plate of ob/ob mice compared to wild type mice(P<0.01). Spearmen analysis showed that body length (axial and appendicular length) is positive related to expression level of estrogen receptor α in growth plate. Three-week-old female ob/ob mice are randomized divided into three groups: (1) ob/ob + ctrl, (2) ob/ob + ERα antagonist (MPP), and (3) ob/ob + ERβ antagonist (PHTPP). Age-matched C57BL/6 mice were also divided into three groups as the groups of ob/ob mice. MPP and PHTPP were administered by intraperitoneally injection for 6 weeks. However, results of X-ray and HE staining demonstrate that leptin deficiency seems disturbs the regulating effects of ER antagonists on longitudinal bone growth. These findings suggested that region-specific expression of ERα might be associated with contrasting phenotypes of axial and appendicular bone growth in ob/ob mice. However, ERs signaling on longitudinal bone growth were blunted by leptin deficiency in ob/ob mice, and the underlying association between ERs and leptin is needed to be explored in future work.